Molecular Simulation of CH4 Nanoscale Behavior and Enhanced Gas Recovery in Organic-Rich Shale. (7th March 2022) - Li, Yang; Lu, Lize; Zhu, Jingyi; Yang, Zhaozhong; Qu, Jianhua; Xue, Heng; Ouyang, Jingyun
Abstract : Occurrence and transport are two important nanoscale behaviors in the exploitation of shale gas. Nanopores in a realistic shale organic matrix are composed of kerogen molecules, which will have a great impact on surface-gas interactions and gas nanoconfined behavior. Although there are previous studies, the physics of gas transport through shale systems remains ambiguous. In this work, cylindrical nanopore models representing different pore sizes and organic-rich shale were constructed. By applying the molecular dynamics simulation method, the occurrence characteristics and transport characteristics of CH4 in the nanopores of organic-rich shale were studied. At last, the process of the adsorbed CH4 displaced by CO2 and N2 in shale nanopores at the subsurface condition was explored. This work can provide a better understanding of gas nanoscale behavior in shale systems and assist the future design of the CO2 sequestration and enhanced gas recovery technique.